Pengaruh Current Ratio, Return On Asset (ROA) dan Debt To Equity Ratio (DER) Terhadap Harga Saham dengan Nilai Perusahaan Sebagai Variabel Moderasi pada Perusahaan Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia (BEI)Tahun 2021 – 2024 - Wiwin Puspitasari; Sintia Safrianti; Fauzan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the simultaneous and partial effects of Current Ratio (CR), Return on Asset (ROA), and Debt to Equity Ratio (DER) on stock prices, while considering the role of Firm Value as a moderating variable. The sample consists of banking sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021 to 2024 period, selected using a purposive sampling method. Secondary data were obtained from annual financial statements, and hypothesis testing was conducted using panel data regression analysis and Moderated Regression Analysis (MRA) through E-Views 13. The results indicate that the Debt to Equity Ratio (DER) has a positive and significant effect on stock prices, whereas the Current Ratio (CR) and Return on Asset (ROA) show no significant impact. Furthermore, Firm Value is proven to moderate the relationship between Debt to Equity Ratio (DER) and stock prices but does not moderate the influence of Current Ratio (CR) and Return on Asset (ROA). These findings offer valuable implications for corporate management and investors in making financial decisions based on fundamental financial indicators.